Construction and Validation of a Generational Identity Scale on Bangladeshi Older Adults - Islam, Azharul; Haque, Shamsul (Frontiers in Psychology, 2021)
There is a lack of a psychometric tool for generational identity. We have conducted two studies involving Bangladeshi older adults who have witnessed the Bangladesh liberation war in 1971 to develop a new generational identity scale (GIS). The first study (N=300) prepared an initial pool of 31 items and got them vetted by expert judges, which retained 21 items to form the provisional GIS (GIS-21). An exploratory factor analysis on GIS-21 excluded eight items and offered a two-factor solution: (i) identification with the generation and (ii) awareness of the generational importance. The second study (N=176) ran a confirmatory factor analysis on the resulting GIS-13 and dropped another item to achieve a better model fit (SRMR =.058, GFI =.986, AGFI =.980 and NFI=.980). The remaining 12-item GIS (GIS-12) showed excellent reliability (Mc Donald’s omega =.898) and satisfactory temporal stability (ICC =.59, 95% CI =0.27 to 0.77) over a 4-week interval. The scale’s moderate correlation with another measure for generational identification demonstrates its convergent validity. Participants’ transitional experience caused by the Bangladesh independence war in 1971 was also moderately correlated with the GIS-12 supporting further theoretical convergence of this scale. We recommend that researchers could use this scale on different populations and age groups upon appropriate validation.